Pre and post tonsillectomy status of serum antistreptolysin o titre in chronic tonsillitis patients - Dutta, Pushan; Nath, Nandita; Dutta, Smrity Rupa Borah (International Journal of Research in Medical Sciences, 2025)
Background: Tonsillitis is a very common disease, more prevalent in children and can be caused by a variety of microbes, out of which group A beta hemolytic Streptococcus (GABHS) is the most common. GABHS infection leads to elevated ASO titre in patient’s serum which may lead to several systemic complications if left untreated. The aim was to find out the prevalence of elevated ASO titre in patients with chronic tonsillitis and to analyse the impact of doing tonsillectomy in lowering the serum ASO titre. Methods: A prospective observational study was carried out on 70 patients during a period of 1 year, who were admitted in ENT ward, Silchar Medical College and Hospital and were planned for tonsillectomy. Serum ASO titre was measured pre-operatively and on every follow-up at 1, 3 and 6 months post-operative period. Results: Out of 70 patients, 26 were positive (37%) for ASO tire pre-operatively. There was not much improvement of ASO titre at 1 month after surgery but 3 months onwards there was significant reduction in ASO-titre level and at 6 months 21 of the 26 (80.7%) patients became negative for serum ASO titre. Conclusions: In our study, we have found that tonsillectomy in indicated patients with raised ASO-titre has a significant role in reducing the titre level post-operatively and thus it prevents serious complications of streptococcal infections like rheumatic fever, glomerulonephritis etc.